2021
DOI: 10.1007/s13593-021-00703-1
|View full text |Cite
|
Sign up to set email alerts
|

Combining crop diversification practices can benefit cereal production in temperate climates

Abstract: Diversifying cropping systems by increasing the number of cash and cover crops in crop rotation plays an important role in improving resource use efficiency and in promoting synergy between ecosystem processes. The objective of this study was to understand how the combination of crop diversification practices influences the performance of arable crop sequences in terms of crop grain yield, crop and weed biomass, and nitrogen acquisition in a temperate climate. Two field experiments were carried out. The first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…These services potentially reduce the dependence on external inputs while maintaining high crop yields and production stability 1 , 4 . Diversification through the inclusion of legumes in cereal-, root-, or tuber-based cropping systems represents a key strategy for sustainable agriculture 3 , 5 , 6 . However, legume cultivation has declined globally in recent decades due to their low and unstable yields, leading to reduced high-quality protein production and loss of ecosystem services 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%
“…These services potentially reduce the dependence on external inputs while maintaining high crop yields and production stability 1 , 4 . Diversification through the inclusion of legumes in cereal-, root-, or tuber-based cropping systems represents a key strategy for sustainable agriculture 3 , 5 , 6 . However, legume cultivation has declined globally in recent decades due to their low and unstable yields, leading to reduced high-quality protein production and loss of ecosystem services 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the legume companion is expected to supplement some of the nutrient requirements with time and the tendency of increased fixation of nitrogen from the atmosphere somewhat meets this expectation. This tendency reflects the interspecies interaction in intercrops of cereals and legumes, where the cereal most often acquires a larger proportion of the soil N in comparison to its proportional abundance, which leads to increased N 2 fixation in the grain legume crop (Rodriguez et al 2021). On the other hand, Li et al (2019) identified a need for fertilisation to support the development of IWG in the establishment phase when intercropped with alfalfa, possibly indicating that alfalfa is too aggressive for intercropping with IWG, at least when established at the same time point.…”
Section: Nitrogen Concentration In Dry Matter and N Accumulationmentioning
confidence: 99%
“…Similarly, multi-species living mulch could offer advantages compared to a mono-specific living mulch. Especially in the period between two crops, when the living mulch acts like a cover crop, specific interactions could lead to greater biomass production or N fixation compared to a mono-specific cover like it is the case for annual cover crops (Wendling et al 2017;Rodriguez et al 2021) During the growing period of the cereal on the other hand, increasing inter-and intra-specific variation must not result in a living mulch with a greater ability to exploit the resources and in a stronger competition with the cereal crop. Indeed, the presence of various species and/or cultivar within the canopy might contribute to the required tradeoff between fast covering the ground for preventing weeds and limiting maximum production for reducing competition for light.…”
Section: Multi-species Mulchmentioning
confidence: 99%